Demethoxycurcumin induces apoptosis in HER2 overexpressing bladder cancer cells through degradation of HER2 and inhibiting the PI3K/Akt pathway. Issue 11 (22nd July 2021) - Kao, Chien‐Chang; Cheng, Yi‐Ching; Yang, Ming‐Hsin; Cha, Tai‐Lung; Sun, Guang‐Huan; Ho, Chi‐Tang; Lin, Ying‐Chao; Wang, Hao‐Kuang; Wu, Sheng‐Tang; Way, Tzong‐Der
Abstract: Bladder cancer is the most common malignancy of the urinary tract and arising from the epithelial lining of the urinary bladder. Resistance to cytotoxic therapies is associated with overexpression of oncogenic proteins; including HER2, and Akt in chemotherapy resistance of bladder cancer. Various studies demonstrated that curcuminoids, the most important active phenolic compounds of turmeric ( Curcuma longa ), have anti‐tumor activities in a wide range of human malignant cell lines. The aim of this study is to evaluate whether curcuminoids (curcumin, demethoxycurcumin (DMC), and bisdemethoxycurcumin) could repress the expression of HER2 in HER2‐overexpressing bladder cancer cells. Among the test compounds, DMC significantly suppressed the expression of HER2, and preferentially inhibited cell proliferation and induced apoptosis in HER2‐overexpressing bladder cancer cells. DMC decreases HER2 level through inhibiting the interaction of HER2 and Hsp90. Our study also indicated that DMC showed additive activity in combination with chemotherapeutic agents, including paclitaxel and cisplatin. These findings show that DMC should be developed further as a new antitumor drug candidate for treatment of HER2‐overexpressing bladder cancer.